The Development of Experiment-Based Physics Worksheets in Science in Developing Students' Science Process Skills - Haerani Haerani; Muhammad Arsyad; Khaeruddin Khaeruddin (Postgraduate, University of Mataram, 2023)
Experiment-based research on the development of student worksheets (SW) in Science Physics has been carried out to Grow Students' Science Process Skills. This study aims to produce a valid, practical, and effective experimental-based student worksheet product. The research method used is the method of research and development (Research and Development). Experiment-based student worksheet development uses the ADDIE model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The students involved in this study were 32 class VIII students at SMPN 51 Makassar and 7 Physics Educators who joined the MGMP IPA in the city of Makassar. The research instruments used were expert validity questionnaires, educator response questionnaires, and science process skills tests. After analyzing the validation data according to Aiken's, an expert agreement index was obtained for scientific literacy-based worksheets of 0.79, an expert response questionnaire index of 0.80, and an expert agreement index of science process skills tests of 0.83 so that all three were declared valid. Practitioners' assessment obtained an overall percentage of 90.80% which is in the very good category. Meanwhile, in terms of science process skills, students who achieve mastery learning are 75% and those who do not achieve completeness are 25%. So that it can be stated that experimental-based worksheets in science learning physics are effective for growing students' science process skills